Effect of Canolla oil on productional traits in Japanies equail - Mohammed, Murad Kazem; Razouki, Raad Hatem; Ibrahim, Youssef Tawfiq; Ahmed, Mohammed Jabbar (Journal of agricultural, environmental and veterinary sciences, 2018)
Total of 150 birds of Japanese quail at 7 weeks of age were fed on five experimental diets for 12 weeks، contain different levels levels addition of canolla oil(0، 25، 50، 75، 100 ml/ Kg diet) to diet in productional traits of Japanies equail and the quality of producted eggs. The productional traits were conclude: egg production، egg weight، food intake، feed conversion coefficient. The 1st diet were used as control، 2nd & 3rd diets had 0.25% & 0.50% of Canolla oil the 4th & 5th diets were included 0.75% & 1% Canolla oil. The birds were randomly distributed into five treatments، each treatment with three replicates (10birds/rep). Results shoued no significant differences (P>0.05) in egg weight، egg production and food conversion ratio between the 1st and 4th، 5th diets while these parameters values were significantly reduced (P<0.05) at the 2nd & 3rd diets compared with 1st diet. However the results of this study indicated the possibility of using Canolla oil in the diet of Japanese quail under same condition of this trail without any effects on growing and egg production.